Light therapy for sleep disturbance comorbid depression in relation to neural circuits and interactive hormones—A systematic review - Yaodong, Chen; Zhang, Yingzi; Feng, Guo; Lei, Yuanfang; Liu, Qiuping; Liu, Yang (PloS one, 2023)
To provide an overview of the evidence on the effect of light therapy on sleep disturbance and depression, identify the light-active neural and hormonal correlates of the effect of light therapy on sleep disturbance comorbid depression (SDCD), and construct the mechanism by which light therapy alleviates SDCD. Articles published between 1981 and 2021 in English were accessed using Science Direct, Elsevier, and Google Scholar following a three-step searching process via evolved keywords. The evidence level, reliability, and credibility of the literature were evaluated using the evidence pyramid method, which considers the article type, impact factor, and journal citation report (JCR) partition. A total of 372 articles were collected, of which 129 articles fit the inclusion criteria and 44% were at the top of the evidence pyramid hierarchy; 50% were in the first quarter of the JCR partitions. 114 articles provided specific neural and hormonal evidence of light therapy and were further divided into three groups: 37% were related to circadian regulation circuits, 27% were related to emotional regulation circuits, and 36% were related to hormones. First, neural and hormonal light-active pathways for alleviating sleep disturbance or depression were identified, based on which the neural correlates of SDCD were located. Second, the light responses and interactions of hormones were reviewed and summarized, which also provided a way to alleviate SDCD. Finally, the light-active LHb and SCN exert extensive regulation impacts on the circadian and emotional circuits and hormones, forming a dual-core system for alleviating SDCD.